Pengembangan Bisnis Totebag sebagai Alternatif Usaha untuk Mengurangi Limbah Plastik - Florencia, Livia Evangelina; Princella, Angellia; Anjelina, Melisa; Barus, Reiko Misha; Darmawan, Veren; Rembulan, Glisina Dwinoor (Jurnal Pengabdian dan Kewirausahaan, 2024)
Plastic waste is a difficult material to recycle, thus posing a threat to the environment. TotenewBag (TnB) aims to create a clean environment free from rampant plastic waste, particularly evident in plastic bags that are highly resistant to decomposition. TnB also has a mission to generate new employment opportunities, foster the creativity of today's youth, and instill pride in their creative endeavors. With this innovation, it is hoped that the use of tote bags will become a positive step for both women and men. Considering the versatile functionality of tote bags, they can serve as eco-friendly shopping bags, replacing the need for plastic bags during shopping. Through this innovation, TnB aspires to reduce the prevalence of plastic bag usage in Indonesia.